Carotid Artery Intimal Medial thickness in Diabetic and Non-Diabetic Subjects in Central Kerala - Sholy K Vareed; Don Paul Mathew; P Suresh (Asian Journal of Medical Radiological Research, 2020)
Background: Increase in intimal medial thickness (IMT) of the carotid arteries is contemplated as a guide to atherosclerotic vascular disease and subclinical organ damage and foretell cardiovascular disease. The study aimed to analyse IMT in non-diabetic and diabetic subjects. Subjects and Methods: There were 105 diabetic and 95 non-diabetic subjects in this study. Common carotid artery (CCA) IMT was calculated using a linear probe of a high-resolution ultrasound medical system. Results: Diabetic subjects (0.95 mm) showed significantly higher mean intimal medial thickness (IMT) when compared non-diabetic subjects (0.85 mm) (p <0.05). Correlation of IMT was seen with age, total cholesterol, triglycerides, HDL & LDL cholesterol and systolic blood pressure (SBP) in diabetic subjects. Total cholesterol, SBP and diastolic blood pressure (DBP) showed a correlation with IMT in the non-diabetic subjects. Age, total cholesterol, SBP, and diabetes were independent risk factors for intimal medial thickness in multivariate linear regression analysis. Conclusion: Higher intimal medial thickness was seen in diabetic subjects when compared to non-diabetic subjects. We conclude that age, total cholesterol, SBP and duration of diabetes showed a significant correlation with IMT. IMT can be considered as a screening tool in diabetic patients for the early detection of atherosclerosis.